(untitled) (Journal of Hama University, 2020)
The aim of this research is to reveal the effect of using the numbered heads strategy in developing critical thinking skills in teaching assets for students of educational qualification diploma in the faculty of education / Tadmur for the academic year (2018-2019). The researcher followed the semi-experimental approach, and to achieve the goal of the research, the researcher prepared a list of critical thinking skills and judged by the competent arbitrators, in addition to the preparation of a note of critical thinking skills based on the pre-determined list. It was applied to the research sample chosen intentionally and consisting of (40) students. On the same group with a time difference between the application of the tool (tribal-post) so that at least (25) days. The data were then collected and analyzed statistically to reveal the following results: _ There are statistically significant differences at the level of significance (0.05) between the average scores of students of the experimental group according to the application of the observation skills of critical thinking (tribal - dimensional), which is attributed to the use of the strategy of numbered heads.